ChemInform Abstract: Palladium‐Catalyzed Oxidative Aminocarbonylation by Decarboxylative Coupling: Synthesis of Alkynyl Amides. Issue 31 (August 2015) - Hwang, Jinil; Choi, Jinseop; Park, Kyungho; Kim, Wonyoung; Song, Kwang Ho; Lee, Sunwoo
Abstract Palladium‐catalyzed aminocarbonylation for the synthesis of alkynyl amides from the coupling reactions of alkynyl carboxylic acids, amines, and carbon monoxide is reported.